A tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst
By growing a needle-shaped copper array on a cheap phosphorus copper net and doping it with tantalum and tungsten, a needle-shaped oxygen evolution catalyst W-Co/Cu-Ta co-doped tantalum tungsten was prepared, which solved the problem of insufficient catalytic performance of 3d transition metal oxides under large current density in the prior art, and achieved high-efficiency oxygen evolution catalytic catalysis in alkaline and neutral electrolytes, reducing production costs and increasing catalytic active sites.
Patent Information
- Application Number
- CN202211732016.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-30
AI Technical Summary
In the prior art, 3d transition metal oxides cannot meet the OER catalytic performance requirements of water decomposition electrodes under industrial conditions under high current density, and Ir and Ru-based oxides have limited their large-scale industrial applications due to their high price, scarce crustal reserves and poor catalytic stability.
By growing a needle-shaped copper array on a cheap phosphorus copper net and doping it into the crystal lattice of needle-shaped copper cobalt by a large atomic radius as a heteroatom, a needle-shaped oxygen evolution catalyst W-Co/Cu-Ta co-doped tantalum and tungsten co-doped tantalum and tungsten co-doped tantalum and tungsten were prepared. The catalyst improves conductivity and hydroxyl adsorption capacity through copper-cobalt needle nanoarrays and tantalum tungsten.
The catalyst exhibits high oxygen evolution catalytic activity in both alkaline and neutral electrolytes, can maintain stable performance under high current density, reduce production costs, and increase catalytic active sites.
Smart Images

Figure CN116005168B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalyst preparation, and relates to an oxygen evolution catalyst, in particular to a tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst. Background Art
[0002] As fossil fuels are depleted and the energy crisis becomes increasingly serious, people are paying more attention to the development of renewable energy. Since the early 1970s, hydrogen has been regarded as an ideal energy source. Hydrogen has the highest energy density among known fuels and is a clean energy source with zero carbon dioxide emissions. Electrolysis of water can also produce oxygen, which is necessary for human survival.
[0003] There are abundant water resources on our planet. If we can use renewable energy sources such as wind and solar energy to generate electricity, we can directly electrolyze water to produce a large amount of clean fuel, which can effectively alleviate the energy crisis. Electrocatalytic water decomposition includes the cathode hydrogen evolution reaction (HER) process involving 2 electron transfer and the anode oxygen evolution reaction (OER) process involving 4 electron transfer. The theoretical equilibrium potential of the HER reaction process is 0V, and the theoretical equilibrium potential of the OER reaction process is 1.23V. Therefore, under normal circumstances, the OER reaction process is more difficult to occur than the HER reaction process. In an alkaline system, due to the reactant OH - The high ion concentration, better stability of non-precious metal-based catalysts, and the fact that the OER reaction does not require the initial H2O molecule dissociation step make the OER reaction performance of electrocatalysts in alkaline systems several orders of magnitude higher than that in acidic conditions. Therefore, the OER reaction process in alkaline systems is more meaningful for practical research.
[0004] In alkaline electrolytes, Ir and Ru-based oxides have excellent OER catalytic performance. However, Ir and Ru-based oxides are expensive, have scarce crustal reserves, and have poor catalytic stability, which limits their large-scale industrial application. Based on this, the research and development of low-cost, high-crustal reserves, and stable non-precious metal-based OER catalysts is a current research hotspot and frontier in the field of electrocatalytic water splitting. 3d transition metal oxides have suitable OER reaction intermediate adsorption energy and are one of the ideal OER electrocatalysts. However, 3d transition metal oxides also have poor conductivity and are not very stable to OH. - Due to the weak adsorption strength of ions, its intrinsic OER catalytic activity needs to be further improved. Especially at high current density, the OER catalytic performance of 3d transition metal oxides is far from meeting the requirements of water splitting electrodes under industrial conditions.
[0005] The electronic structure of 3d transition metal oxides can be regulated by heteroatom doping, which is expected to improve the conductivity of 3d transition metal oxides and make them more resistant to OH. -The adsorption capacity of ions is enhanced, and the adsorption strength of metal active centers to O-containing intermediates such as OH and OOH is optimized, thereby achieving an improvement in the intrinsic catalytic activity of 3d transition metal oxides in OER.
[0006] The present invention uses a copper mesh as a substrate, designs a copper-cobalt needle-shaped nanoarray, and uses tantalum tungsten with a larger atomic radius as a heteroatom doped into the needle-shaped copper-cobalt lattice, which greatly improves the conductivity of the catalyst, is conducive to the adsorption of hydroxyl groups and the desorption of oxygen, and is of great significance to the development of water electrolysis. In addition, the catalyst material prepared by the invention also has a high oxygen evolution catalytic activity in neutral electrolysis PBS. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for growing a needle-shaped copper array on a cheap phosphor copper mesh, and then growing Co, Ta, and W, and proposes a method for preparing a tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst: the method specifically comprises the following steps:
[0008] S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 20-40 minutes;
[0009] S2, using phosphor copper mesh as anode and iron sheet as cathode, growing Cu(OH)2 needle array in 1-2 mol / L NaOH or KOH, in order to prepare needle-shaped copper with larger specific surface area, the present invention introduces 10-20 mA cm between the cathode and cathode. -2 The current, the reaction ion formula is Cu-2e - +2OH - →Cu(OH)2.
[0010] S3. Place the electrode with Cu(OH)2 prepared in step S2 into a tubular furnace, introduce Ar / H2 gas, and calcine at 150-200°C for 20-40min according to the reaction equation Cu(OH)2+H2→Cu+H2O.
[0011] S4. Prepare Co and W solutions: mix 0.1-1g CoSO4·6H2O or CoCl2, 0.1-3g Na2WO4·2H2O, 1-2g C6H5Na3O7·2H2O, and 110-120μL 98% H2SO4 into 40mL distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, and saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is generally 10-35min, then a layer of Co and W elements can be electroplated on the needle-shaped Cu surface.
[0012] S5, take 1.2-3g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol, soak the Cu needle array containing Co and W prepared in step S4 into the tantalum solution, add 0.5-0.8g of urea, heat it in a water bath to 65-75°C, and heat it for 1-3h. Tantalum is doped in this way, and the prepared sample is named W-Co / Cu-Ta. It is used in the field of water electrolysis, and it has good oxygen evolution catalytic activity in both alkaline and neutral solutions.
[0013] Preferably, the phosphor bronze mesh in step S1 is 120 mesh;
[0014] Preferably, the zinc content of the phosphor copper mesh in step S1 is 1-3%;
[0015] Preferably, the step S2 uses 1 mol / L NaOH;
[0016] Preferably, the step S2 uses 2 mol / L KOH;
[0017] Preferably, the calcination temperature in step S3 is 200°C;
[0018] Preferably, the electroplating time in step S4 is 30 minutes;
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention replaces the base material of the foam structure with a cheap metal mesh, which not only reduces the production cost of the catalyst, but also reduces gas resistance and enables large current discharge.
[0021] 2. The catalyst prepared by the present invention is a self-supporting catalyst, and no binder or conductive agent is used, thereby improving the catalytic activity of the material.
[0022] 3. The W-Co / Cu-Ta material prepared by the present invention grows a three-dimensional array in a two-dimensional copper mesh, which greatly increases the catalytic area of the material and is beneficial to improving the catalytic active sites of the material.
[0023] 4. The present invention expands the needle-like structure lattice after co-doping with W and Ta, making it have a lower electron transfer resistance and enhancing conductivity. Doping optimizes the electronic structure of Co, the surface active center, making it easier to promote hydroxyl adsorption and O2 desorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 1 of the present invention.
[0025] Figure 2The transmission electron microscope image and the surface scanning energy spectrum image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 2 of the present invention.
[0026] Figure 3 This is a transmission electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 3 of the present invention.
[0027] Figure 4 This is a transmission electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 3 of the present invention after being subjected to a large current and long-term oxygen evolution test.
[0028] Figure 5 The LSV curves of OER of the W-Co / Cu-Ta oxygen evolution catalyst prepared in Example 4 of the present invention and the oxygen evolution catalysts prepared in Comparative Examples 1-4 were tested in 1 M KOH.
[0029] Figure 6 CV graphs of the catalysts prepared for the phosphorus copper mesh, Example 4 and Comparative Example 1 DETAILED DESCRIPTION
[0030] Exemplary embodiments, features and performance aspects of the present invention will be described in detail below with reference to the accompanying drawings.
[0031] Example 1
[0032] S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 20 minutes. The zinc content of the phosphor bronze mesh is 3% and the mesh size is 20 meshes.
[0033] S2, using phosphor copper mesh as anode and iron sheet as cathode, growing Cu(OH)2 needle array in 1 mol / L NaOH. In order to prepare needle-shaped copper with larger specific surface area, the present invention introduces 10 mA cm between the cathode and cathode. -2 The current, the reaction ion formula is Cu-2e - +2OH - →Cu(OH)2.
[0034] S3, put the electrode with Cu(OH)2 prepared in step S2 into a tube furnace, introduce Ar / H2 gas, and calcine at 150°C for 20-40min according to the reaction equation Cu(OH)2+H2→Cu+H2O.
[0035] S4. Prepare Co and W solutions: mix 0.1g CoSO4·6H2O, 3gNa2WO4·2H2O, 1g C6H5Na3O7·2H2O, and 110μL 98% H2SO4 in 40mL distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, and saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is generally 10min, then a layer of Co and W elements can be electroplated on the needle-shaped Cu surface.
[0036] S5. Take 1.2g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol. Soak the Cu needle array containing Co and W prepared in step S4 in the tantalum solution. Add 0.5g of urea and heat it in a water bath to 65°C for 1h. In this way, tantalum is doped and the prepared sample is named W-Co / Cu-Ta. It is used in the field of water electrolysis and has good oxygen evolution catalytic activity in both alkaline and neutral solutions.
[0037] Figure 1 This is a scanning electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 1 of the present invention. It can be clearly seen from the figure that the morphology of the material is a needle array structure. The material grows a three-dimensional array in the two-dimensional copper mesh, which greatly increases the catalytic area of the material and is beneficial to improving the catalytic activity of the material.
[0038] Example 2
[0039] S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 40 minutes. The zinc content of the phosphor bronze mesh is 1%.
[0040] S2, using phosphor copper mesh as anode and iron sheet as cathode, growing Cu(OH)2 needle array in 2 mol / L KOH. In order to prepare needle-shaped copper with larger specific surface area, the present invention introduces 20 mA cm between the cathode and cathode. -2 The current, the reaction ion formula is Cu-2e - +2OH - →Cu(OH)2.
[0041] S3. Place the electrode with Cu(OH)2 prepared in step S2 into a tubular furnace, introduce Ar / H2 gas, and calcine at 200°C for 40 minutes according to the reaction equation Cu(OH)2+H2→Cu+H2O.
[0042] S4. Prepare Co and W solutions: mix 1g CoCl2, 0.1Na2WO4·2H2O, 2g C6H5Na3O7·2H2O, and 120μL98% H2SO4 in 40mL of distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, and saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is generally 35min, then a layer of Co and W elements can be electroplated on the needle-shaped Cu surface.
[0043] S5. Take 3g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol. Soak the Cu needle array containing Co and W prepared in step S4 in the tantalum solution. Add 0.8g of urea and heat it in a water bath to 75°C for 3h. In this way, tantalum is doped and the prepared sample is named W-Co / Cu-Ta. It is used in the field of water electrolysis and has good oxygen evolution catalytic activity in both alkaline and neutral solutions.
[0044] Figure 2 The transmission electron microscope image and the surface scanning energy spectrum image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 2 of the present invention. It can be seen from the transmission image that the material is a needle-like structure, which is the same as the scanning electron microscope test of the sample prepared in Example 1. It can be seen from the surface scanning energy spectrum that W, Co, Cu, and Ta are evenly distributed on the surface of the needle-like structure, proving that the sample W-Co / Cu-Ta is prepared. However, it is found from the surface scanning energy spectrum that the content of W is less. It is speculated that this is because an ion exchange reaction occurs during the immersion in the tantalum pentachloride solution in step S5, causing a part of W to be dissolved.
[0045] Example 3
[0046] S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 30 min.
[0047] S2, using phosphor copper mesh as anode and iron sheet as cathode, growing Cu(OH)2 needle array in 1.5 mol / L NaOH. In order to prepare needle-shaped copper with larger specific surface area, the present invention introduces 15 mA cm between the cathode and cathode. -2 The current, the reaction ion formula is Cu-2e - +2OH - →Cu(OH)2.
[0048] S3, put the electrode with Cu(OH)2 prepared in step S2 into a tube furnace, introduce Ar / H2 gas, and calcine at 180°C for 25min according to the reaction equation Cu(OH)2+H2→Cu+H2O.
[0049] S4. Prepare Co and W solutions: mix 0.8g CoSO4·6H2O, 2gNa2WO4·2H2O, 1.8g C6H5Na3O7·2H2O, and 118μL 98% H2SO4 in 40mL distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, and saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is generally 25min, then a layer of Co and W elements can be electroplated on the needle-shaped Cu surface.
[0050] S5. Take 1.2g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol. Soak the Cu needle array containing Co and W prepared in step S4 in the tantalum solution. Add 0.7g of urea and heat it in a water bath to 65°C for 1.3h. Tantalum is doped in this way, and the prepared sample is named W-Co / Cu-Ta. It is used in the field of water electrolysis, and has good oxygen evolution catalytic activity in both alkaline and neutral solutions.
[0051] Figure 3 This is a transmission electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 3 of the present invention. As can be seen from the figure, there are black shadows on the surface of the transmission electron microscope image of W-Co / Cu-Ta, which are speculated to be the Co, W, and Ta elements surrounding the Cu needles. These elements surround the Cu needles and can provide more catalytic active sites during the catalytic process. Figure 4 This is a transmission electron microscope image of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 3 of the present invention after a large current and long-term oxygen evolution test. It can be seen from the figure that after the oxygen evolution test, Figure 3 The small dark shadows in the figure become granular, which are circled in the figure. In the oxygen evolution process, the real catalytic active site is the transformation of Co(OH)2 to CoOOH. W and Ta surround it to ensure that the needle-like structure will not be destroyed by large current and large bubbles of O2. This is also the reason why the material has high catalytic stability.
[0052] Example 4
[0053] S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 33 minutes.
[0054] S2, using phosphor copper mesh as anode and iron sheet as cathode, growing Cu(OH)2 needle array in 1.8 mol / L KOH. In order to prepare needle-shaped copper with larger specific surface area, the present invention introduces 17 mA cm between the cathode and cathode. -2 The current, the reaction ion formula is Cu-2e - +2OH - →Cu(OH)2.
[0055] S3. Place the electrode with Cu(OH)2 prepared in step S2 into a tubular furnace, introduce Ar / H2 gas, and calcine at 180°C for 28 minutes according to the reaction equation Cu(OH)2+H2→Cu+H2O.
[0056] S4. Prepare Co and W solutions: mix 0.9g CoCl2, 2.2g Na2WO4·2H2O, 1.3g C6H5Na3O7·2H2O, and 105μL98% H2SO4 in 40mL distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, and saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is generally 22min, then a layer of Co and W elements can be electroplated on the needle-shaped Cu surface.
[0057] S5. Take 2.6g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol. Soak the Cu needle array containing Co and W prepared in step S4 in the tantalum solution. Add 0.6g of urea and heat it in a water bath to 69°C for 2.1h. Tantalum is doped in this way, and the prepared sample is named W-Co / Cu-Ta. It is used in the field of water electrolysis, and has good oxygen evolution catalytic activity in both alkaline and neutral solutions.
[0058] S6. The W-Co / Cu-Ta catalyst prepared in step S5 was used as an oxygen evolution catalyst and OER tests were performed in 1M KOH and phosphate buffered saline (PBS), respectively. Mercuric oxide was used as a reference electrode in the 1M KOH (pH=14) test, and saturated calomel was used as a reference electrode in the PBS (pH=7.0) test.
[0059] Comparative Example 1: Except that 2.2 g of Na2WO4·2H2O is not added in step S4, the remaining steps are the same as those in Example 4.
[0060] Comparative Example 2: Except that tantalum pentachloride is not added in step S5, the other steps are the same as those in Example 4.
[0061] Comparative Example 3: Except that 2.2 g of Na2WO4·2H2O is not added in step S4 and tantalum pentachloride is not added in step S5, the remaining steps are the same as those in Example 4.
[0062] Comparative Example 4: Except that tantalum pentachloride is not added in step S5, the other steps are the same as those in Example 4.
[0063] Figure 5The LSV curves of the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 4 of the present invention and the oxygen evolution catalyst prepared in Comparative Examples 1-4 were tested in 1M KOH for OER. The curves are converted results, and the conversion formula is: E = E 测 +0.05916*pH-1.23. It can be seen from the figure that the oxygen evolution catalyst W-Co / Cu-Ta prepared in Example 4 has the highest catalytic activity. The catalyst performance of Comparative Example 3 without Ta and W is the worst. The LSV curves of Comparative Example 2 and Comparative Example 4 are relatively close. The guessed mechanism is that the absence of urea is not conducive to the doping of Ta, and urea plays a certain role in promoting the doping of Ta in step S5. Comparative Example 1 is a material without W, and its performance is also worse than that of the sample prepared in Example 4. In summary, in the oxygen evolution catalytic process of the present invention, W and Ta are indispensable, and the two have a synergistic effect, which together ensure that W-Co / Cu-Ta has a higher catalytic activity. Figure 6 The CV graphs of the phosphor copper mesh, Example 4 and Comparative Example 1 show that the CV area of the phosphor copper mesh is much smaller than that of the catalyst material prepared in Example 4 and Comparative Example 1. This proves that it is feasible to increase the electrochemical active area of the material using a needle array, and the present invention also increases the active sites of the catalyst through W, Co and Ta. This promotes the development of the water electrolysis hydrogen production industry to a certain extent.
[0064] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solution described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solution to deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst, characterized in that: The specific preparation method is as follows: S1. Place the purchased phosphor bronze mesh in 3M HCl and anhydrous ethanol for ultrasonic cleaning for 20-40 minutes; S2, using phosphor copper mesh as anode and iron sheet as cathode, grow Cu(OH)2 needle array in 1-2 mol / L NaOH or KOH. In order to prepare needle-shaped copper with larger specific surface area, 10-20 mA cm is introduced between the cathode and cathode. -2 The current; S3, placing the electrode with Cu(OH)2 prepared in step S2 into a tubular furnace, introducing Ar / H2 gas, and calcining at 150-200°C for 20-40min; S4, prepare Co and W solutions: mix 0.1-1g CoSO4·6H2O or CoCl2, 0.1-3g Na2WO4·2H2O, 1-2g C6H5Na3O7·2H2O, and 110-120μL 98% H2SO4 into 40mL distilled water, use the needle-shaped Cu array prepared in step S3 as the working electrode, use saturated calomel as the reference electrode, adjust the voltage of the three-electrode system to -1.9V, and the electroplating time is 10-35min; S5, take 1.2-3g of tantalum pentachloride and dissolve it in 50ml of anhydrous ethanol, immerse the Cu needle array containing Co and W prepared in step S4 into the tantalum solution, add 0.5-0.8g of urea, heat it in a water bath to 65-75°C, and heat it for 1-3h. In this way, tantalum is doped, and the prepared sample is named W-Co / Cu-Ta; The phosphor bronze mesh in step S1 is 120 meshes; the zinc content of the phosphor bronze mesh in step S1 is 1-3%.
2. The tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst according to claim 1, characterized in that: The step S2 uses 1 mol / L NaOH.
3. The tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst according to claim 1, characterized in that: The step S2 uses 2 mol / L KOH.
4. The tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst according to claim 1, characterized in that: The calcination temperature in step S3 is 200°C.
5. The tantalum-tungsten co-doped needle-shaped oxygen evolution catalyst according to claim 1, characterized in that: The electroplating time in step S4 is 30 minutes.
Citation Information
Patent Citations
Preparation method of electrolyzed water anode with cobalt-nickel composite copper substrate
CN113832476A
Cited By
Nickel-tantalum alloy catalytic electrode, preparation method and application thereof
CN122543077A